Pengaruh Komunikasi terhadap Kinerja Pegawai melalui Kemampuan Kerja sebagai Variabel Intervening pada Dinas Pemberdayaan Perempuan, Perlindungan Anak dan Pengendalian Penduduk Provinsi Jambi - Nur Azizah; Sumarni SumarniSumarni; Dian Mala Fithriani Aira (Lembaga Yasin AlSys, 2026)
Employee performance is an important factor in supporting the success of public sector organizations, particularly at the Office of Women’s Empowerment, Child Protection, and Population Control of Jambi Province. Optimal performance needs to be supported by effective communication and adequate work ability so that task implementation and public services can be carried out professionally. This study aims to analyze the effect of communication on employee performance through work ability as an intervening variable. This study uses a quantitative method with a descriptive approach. The research population included all employees of the Office of Women’s Empowerment, Child Protection, and Population Control of Jambi Province, totaling 53 people, with a saturated sampling technique. Data were collected through observation, documentation, and questionnaires, and were then analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that employee performance was in the high category, communication was classified as very good, and work ability was in the capable category. The SEM-PLS analysis results prove that communication has a positive and significant effect on employee performance and work ability. In addition, work ability has a positive and significant effect on employee performance and is proven to mediate the effect of communication on employee performance. The conclusion of this study affirms that improving communication and work ability plays an important role in promoting more professional, productive, and effective employee performance in achieving institutional goals. The implications of this study indicate the need to strengthen organizational communication patterns and develop employees’ work ability as a strategy for improving the performance of public sector apparatus.